A assistência estudantil no IFPR (2015-2019): avaliação da efetividade do PNAES, entre os estudantes em situação de vulnerabilidade socioeconômica no campus Palmas - PR - Carvalho, Marinez de (2020)
PNAES is the most comprehensive Student Assistance program in Brazil. It was created in 2007 and implemented in 2008, with the purpose of “expanding the conditions for young people to stay in federal public higher education” (BRASIL, 2010a). Based on the reality of students in IFPR campus Palmas and in the purpose of PNAES, this research proposes to analyze the implementation of PNAES in IFPR, in the light of decree nº 7234/2010 and, based on the experience of the Palmas campus, to evaluate the effectiveness of programs of PNAES (PACE, PEA, PIBIS and Monitoring) among students in situations of socioeconomic vulnerability, with regard to the permanence and conclusion of the course, in the period from 2015 to 2019. This study has a qualitative nature and methodologically comprises documentary research. The survey results showed that the implementation of PNAES in IFPR in general is developed in line with Decree No. 7234/2010. Regarding the effectiveness of the PNAES, with regard to the permanence and conclusion of the course among students in a situation of socioeconomic vulnerability, the program proved to be effective in both aspects, since all the criteria presented positive results among the students assisted by the program, proportionally. the percentage of active and graduating students was higher among students assisted by the PNAES, while dropouts, transferred students and those with locked enrollments were lower. However, the rate of dropout, transfer and locking of the undergraduate course is still high on campus and the PNAES does not serve all students who need it.